Effect of intrahepatic cholestasis of pregnancy on infantile food allergy: A retrospective longitudinal study cohort in Southwest China. (May 2022) - Huang, Liqiong; Li, Xin; Liu, Tianjiao; Wei, Lu; Fan, Conghong; Tang, Dongmei; Xiong, Wen; Li, Yalan; Wei, Sumei; Xiong, Zhengai
Abstract: Introduction: Intrahepatic cholestasis of pregnancy has been consistently associated with a higher incidence of adverse pregnancy outcomes. Previous studies mainly focused on the effects of intrahepatic cholestasis of pregnancy on pregnant mothers and fetuses, and few studies reported the postpartum growth and development of fetuses in pregnant women with intrahepatic cholestasis of pregnancy. The aim of this study was to investigate impact of maternal serum total bile acid levels on maternal and neonatal outcomes as well as child growth and food allergy. Material and methods: A retrospective longitudinal cohort investigation was carried out among 751 pregnant women with intrahepatic cholestasis of pregnancy at 30-32 weeks of gestation from the Longitudinal Intrahepatic Cholestasis of Pregnancy Study (LoICPS). Data on the characteristics of the mothers and neonates were collected. Infant growth data and food sensitivities were also collected. Results: In our cohort, the average maternal serum total bile acid level was 35.09±30.02 μmol/L, with 58.8% of mothers suffering from mild intrahepatic cholestasis of pregnancy and 29.2% suffering from severe intrahepatic cholestasis of pregnancy. Positive correlations were found between maternal serum total bile acid levels and twin pregnancy (beta-value: 11.55, 95% CI: 2.89 - 20.20. P = 0.009) and meconium stained amniotic fluid (beta-value: 14.64, 95% CI: 9.41 - 19.87. P < 0.001). In addition, the infants of mothers with severe intrahepatic cholestasis of pregnancy were more likely to be allergic to foods at 6 months. Conclusions: This study suggested that despite pregnant women with intrahepatic cholestasis of pregnancy taking ursodeoxycholic acid tablets and cesarean section before expected date of childbirth, the perinatal outcome of newborns partially improving, the incidence of infantile food allergy was still increased.